2013
DOI: 10.1111/1747-0080.12043
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the diet and the budget: Food purchasing practices of food‐insecure families in New Zealand

Abstract: Aim The aims of this study were to examine total food expenditure and the types of food purchased in food‐insecure households with children, to compare these by severity of food insecurity (moderate or low food security) and furthermore to estimate food expenditure as a percentage of net household income. Methods The study was conducted in Dunedin, New Zealand (NZ) (from June 2009 to May 2010), and included low‐income (≤NZ$45 000/year), food‐insecure households with children (n = 165). The main food preparer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Food-insecure households that had taken part in a previous study (18) were also contacted by mail. Interested participants could contact researchers by a free telephone number or email.…”
Section: Methodsmentioning
confidence: 99%
“…Food-insecure households that had taken part in a previous study (18) were also contacted by mail. Interested participants could contact researchers by a free telephone number or email.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all researchers have concluded that healthy foods are more expensive than unhealthy foods, and, as a percentage of household income, a basket of healthy food costs more for low-income than for high-income families. 3,4,6,[14][15][16] For example, while high-income families need to spend 9% of household income on a basket of healthy foods, low-income families would need to spend 33% of income for the same food basket. 4 This phenomenon was recognised over 100 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with limited access to food often choose food with high caloric value instead of foods with high nutritional value, a contributing factor to weight gain (Alaimo et al, 2001;Burns, 2004;Drewnowski and Specter, 2004;Handforth et al, 2013;Townsend et al, 2001). People experiencing food insecurity are less likely to eat fruit and vegetables at levels recommended for good health (Gulliford et al, 2003;Hume et al, 2009;Kirkpatrick and Tarasuk, 2008;Smith et al, 2013).…”
Section: Introductionmentioning
confidence: 99%